EVALUASI DASAR PENETRATION TESTING MENGGUNAKAN FRAMEWORK MITRE ATT&CK - Vivin Wahyudi; Muhammad Rudyanto Arief; Banu Santoso; Rangga Wahyu Nugroho (Universitas Muhammadiyah Gresik, 2025)
Penetration testing is a method used to identify security vulnerabilities in networks or computer systems. In this process, pentesters attempt to exploit security gaps by simulating potential attacks that could be carried out by an actual attacker. The goal of penetration testing is to evaluate the security of computer systems or networks. This multi-stage approach, which includes information gathering, exploitation, and post-exploitation, utilizes the MITRE ATT&CK framework. Tools are used to help identify and exploit security weaknesses, such as nmap, netdiscover, metasploit, SSH, and MySQL. This research can reduce the risk of data loss and operational disruptions, enhance pentesters' skills and awareness, and strengthen the security of computer systems and networks.